Analysis and optimization of coil structure of magnetic circuit mechanism for electric vehicle wireless charging system. Issue 1 (February 2021) - Wang, Songcen; Xu, Chong; Wei, Bin; Xu, Jinxing; Yin, Jiacheng; Xia, Chenyang
Abstract: To improve the efficiency of the electric vehicle wireless charging system, an optimization design method for the number of coil layers is proposed and studied, which effectively improves the coupling coefficient of the magnetic circuit mechanism. This article first analyzes the energy efficiency characteristics of the wireless charging system for electric vehicles. Then, it analyzes the inductance value changes and magnetic field distribution characteristics of fixed turns coils under different layers. The finite element simulation results performed by MAXWELL show that inducing the number of primary coil layers and increasing the number of secondary coil layers are conducive to the improvement of the coupling coefficient between the coils. Then, based on the theoretical analysis results, the number of coil turns of each layer of the multilayer coil is analyzed and optimized, and a bowl-shaped pair multilayer coil winding method is proposed.